2014
DOI: 10.1016/j.newast.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A γ Doradus candidate in eclipsing binary BD And?

Abstract: The BVR photometric light curves of the eclipsing binary BD And were ob-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…The existence of a third component on a long-period orbit was first indicated by the timing variability and third light in the LC modeling (see Sipahi & Dal, 2014). Our new spectroscopy conclusively shows the presence of an additional component.…”
Section: Third Component and The Outer Orbitsupporting
confidence: 70%
See 1 more Smart Citation
“…The existence of a third component on a long-period orbit was first indicated by the timing variability and third light in the LC modeling (see Sipahi & Dal, 2014). Our new spectroscopy conclusively shows the presence of an additional component.…”
Section: Third Component and The Outer Orbitsupporting
confidence: 70%
“…BD And was identified as a ROSAT source by Shaw et al (1996), and it was detected by Swift (Evans et al, 2013) and twice in the course of the XMM-Newton Slew Survey (XMM-SSC, 2018), indicating that the source has a high level of magnetic activity. Only recently, Sipahi & Dal (2014) obtained CCD BV R photometry of the system and found that (i) the true orbital period is two times longer than determined previously, (ii) the mass ratio of the eclipsing binary is about 0.97, (iii) minima times show a cyclic variability indicating presence of a third body on about 9.6-year orbit, and (iv) light variation outside the primary eclipse may result from γ Dor oscillations of the primary component. Subsequently Kim et al (2014) analyzed extensive new BV R photometry as well as published timing data.…”
Section: Introductionmentioning
confidence: 99%
“…Aerts et al (2002) report the detection of δ Sct pulsations in the 1.15-day orbit ellipsoidal binary XX Pyx. Dal & Sipahi (2013) report the detection of δ Sct oscillations in the 0.69-day orbit ellipsoidal binary V1464 Aql, and Sipahi & Dal (2014) orbit near-contact binary V392 Ori. From the present study, the ten systems displaying γ Dor and/or δ Sct with P orb < 0.5 day are odd as no oscillations have been detected so far, as far as we know, in such short period systems.…”
Section: Classical Pulsatorsmentioning
confidence: 99%
“…Its properties are relatively poorly known compared to those of other short-period binaries. There is no spectroscopic study for BD And in the literature [40]. The photometric lightcurves of BD And in the BVR-bands were observed in 2008 and 2009 [40].…”
mentioning
confidence: 99%
“…There is no spectroscopic study for BD And in the literature [40]. The photometric lightcurves of BD And in the BVR-bands were observed in 2008 and 2009 [40]. Using these observations authors determined the photometric solution of BD And.…”
mentioning
confidence: 99%